Pendidikan Berbasis Merdeka Belajar Dalam Al-Qur’an : (Q. S Al-Alaq/ 96: 1-5, Q.S. Mujadalah/58: 11) - Maisarah Maisarah; Liza Annisa; Annisa Dahlila Angelina; Amiruddin Siahaan; Amiruddin Amiruddin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Education as an investment in the future has an important role in building the nation. The goal is an ideal to be achieved by implementing an activity. No activity is programmed without a goal because it is something that has no certainty in determining which direction the activity will be carried out. Globally the purpose of learning is a change in a person for the better. The concept of independent learning is very different from the existing curriculum used by formal education in Indonesia. This new educational concept considers students' individual cognitive abilities and uniqueness. The method used is the method of literature. Content analysis is used to analyze research data. With the independent learning program, it is hoped that the class atmosphere will be more fun and happy. This certainly affects the quality of learning better. A pleasant learning atmosphere can increase student enthusiasm for learning, and teachers and parents can also feel it.